2012
DOI: 10.1186/1477-7819-10-233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the metastatic status of lymph nodes identified using axillary reverse mapping in breast cancer patients

Abstract: BackgroundAxillary reverse mapping (ARM) is a new technique to preserve upper extremity lymphatic pathways during axillary lymph node dissection (ALND), thereby preventing lymphedema patients with breast cancer. However, the oncologic safety of sparing the nodes identified by ARM (ARM nodes), some of which are positive, has not been verified. We evaluated the metastatic status of ARM nodes and the efficacy of fine needle aspiration cytology (FNAC) in assessing ARM node metastasis.MethodsSixty patients with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…The positive RAM node was identified in pN3 axilla(high stage axillary disease). The same pattern had been described in various studies in literature, which have shown a positive relation between high nodal positivity and chance of arm lymphatics also being involved by the disease [9,10,17,19,20] Schunemann Jr et al, found a statistically significant association between occurrence of metastasis in RAM nodes and high nodal disease(P<.0.001) [19]. Most studies thus suggest that performing RAM in patients with high nodal disease, is not oncologically sound [10,11,17,19] .…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The positive RAM node was identified in pN3 axilla(high stage axillary disease). The same pattern had been described in various studies in literature, which have shown a positive relation between high nodal positivity and chance of arm lymphatics also being involved by the disease [9,10,17,19,20] Schunemann Jr et al, found a statistically significant association between occurrence of metastasis in RAM nodes and high nodal disease(P<.0.001) [19]. Most studies thus suggest that performing RAM in patients with high nodal disease, is not oncologically sound [10,11,17,19] .…”
Section: Discussionsupporting
confidence: 52%
“…In our study, using methylene blue dye injection, at the start of surgery, blue lymphatics were identified in72.2 % while blue lymph nodes could be identified in 61.1%.The pattern of distribution of arm lymphatics in axilla varies with respect to axillary vein . Bonetti et al described 5 common variations in the distribution of arm lymphatics in the axilla [6], with most of the lymphatics and lymph node being found within the region formed by inferior margin of axillary vein and the second intercostobrachial nerve and thoraco dorsal pedicle [4,5,11,17].In our study, 69.2% of the identified arm lymphatics was within one cm inferior to axillary vein, lateral to thoraco dorsal pedicle.RAM lymphatics were successfully identified in 10 of 13 patients with negative axilla, in 2/2 patients with pN1 disease but only in 1/3 patients with pN3 disease. This may be postulated to be secondary to lymphatic obstruction by extensive disease in axilla as described in literature [9,18] .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Some showed a positive view of the benefits and morbidity reduction by using this technique, even though further studies are necessary to affirm anything (Gobardhan et al, 2012) others defend the use of this technique in all cases, except in patients whose sentinel lymph node (SLN) is too close to the ARM lymph node and when there are too many compromised nodes (Boneti et al, 2009) and there are some who question the real effectiveness and therapeutic safety of this technique (Ikeda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%